Type 2 Diabetes Mellitus: Mini Review: The Role of Genetic Polymorphism in Type 2 Diabetes Mellitus (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder that is characterized by hyperglycemia (high blood sugar) in the context of insulin resistance and relative lack of insulin. Type 2 diabetes is caused by a combination of lifestyle and genetic factors .Some of these factor are such as diet and obesity, are under personal control while other factors such as increasing age, female gender, and genetic are beyond control. In this review we hypothesize the role of genetic polymorphism in gene Association of Rho Guanine Nucleotide Exchange Factor 11 (ARHGEF11), NOD-Like Receptor Family Pyrin Domain Containing 3 (NLRP3), Low –Density Lipoprotein Receptor-Related Protein 5 (LRP5), Toll Like Receptor 4 (TLR4) and the risk of Type 2 Diabetes Mellitus.